Promotional Strategy to Increase Sales on Sahabat Pharmacy - Siara, Sabina; Aprianingsih, Atik (Jurnal Pendidikan Indonesia, 2025)
This study evaluates and enhances the promotional strategies of Apotek Sahabat Samarinda or also known as Sahabat Pharmacy to increase sales within the competitive pharmaceutical market of Samarinda, Indonesia. A quantitative research approach was employed to gather primary data via surveys from 385 respondents, aimed at evaluating customer behavior, preferences, and reactions to various marketing strategies. This research employs the Integrated Marketing Communications (IMC) framework, emphasizing advertising, sales promotion, public relations, direct marketing, and personal selling. The results indicate that promotional strategies have a substantial effect on customer attitudes and purchase intentions. Sales promotions, direct marketing, and personal selling demonstrated the most significant positive impact on customer perceptions. The study emphasizes the necessity of customizing promotional strategies to address customer needs and enhance customer engagement. It is recommended that Sahabat Pharmacy enhance its digital marketing initiatives, improve product bundling strategies, and establish a customer loyalty program to promote sustained sales growth and enhance customer satisfaction. This study enhances the understanding of the impact of promotional strategies on sales performance within the pharmacy sector.